Cervical squamous intraepithelial lesions grades 1 and 2: value of an alternative morphological classification and of p16 immunohistochemistry in the prediction of clinical outcome - Rafael C. Salim; Tatiana M. Lima; Thais Heinke; Karla C. K. Prigenzi; Neila Maria G. Speck; Gustavo R. A. Focchi (Sociedade Brasileira de Patologia Clínica, 2017)
ABSTRACT Introduction: Diagnostic reproducibility and determination of prognostic factors in cervical intraepithelial neoplasias grades 1 and 2 are still relevant problems in the daily practice of gynecological histopathology. Objective: To correlate the value of morphological reclassification and of p16 immunoexpression in cervical intraepithelial neoplasias grades 1 and 2 with clinical outcome. Materials and methods: Sixty-six patients were included (34 with cervical intraepithelial neoplasia grade 1, and 32 with grade 2); an immunohistochemical study with p16 and reclassification according to the Lower Anogenital Squamous Terminology (LAST) Consensus and by the alternative proposal of Herfs and Crum were done; unfavorable outcome was defined as a subsequent histologic diagnosis of cervical intraepithelial neoplasia grade 3 or invasive squamous cell carcinoma. Results: We observed superior performance of the alternative morphological classification (p = 0.002) to determine unfavorable outcome. We also detected superior performance of p16 in the same determination (p = 0.002). Conclusion: The use of an alternative morphological classification is promising; in the context of the use of immunohistochemical antibodies as biomarkers, p16 showed good sensitivity and negative predictive value in the determination of cases in which the outcome was unfavorable.